Convergence in International public sector accounting rules in Colombia: An aproximation to the peruvian case - Montilla Galvis, Omar de Jesús (2019)
Under the phenomenon of globalization there are many practices that have been generalized at the governmental level, one of them is the process of convergence of the International Public Sector Accounting Standards (IPSAS) to Accounting Information Systems in Latin American countries, which have given greater prominence to the National Accounting and have facilitated the control processes to the governmental management in their national and territorial levels. This article makes a comparative analysis of the convergence process experienced by the countries of Peru and Colombia, with the main reference being the document constructed by the Inter-American Development Bank (IDB) and the Forum of Government Accounting of Latin America (FOCAL) called Government Accounting in Latin America and Convergence to International Public Sector Accounting Standards (IPSAS) , recently published in the countries of the region; Additionally, it details a basic analysis regarding the variations observed for the Department of Valle del Cauca (Colombia) in the public accounting information for the years 2015 to 2018 to analyze the happened in the convergence process in the balance of this territory.